QM/MM molecular modelling on mutation effect of chorismate synthase enzyme catalysis - Lawan, Narin; Chasing, Pongsakorn; Santatiwongchai, Jirapat; Muangpil, Sairoong (Journal of molecular graphics & modelling, 2019)
Chorismate synthase (CS) catalyzes the conversion of 5-enolpyruvylshikimate-3-phosphate (EPSP) to chorismate which is a key intermediate in the biosynthesis of aromatic amino acids. CS enzyme is a new target for antibacterial drugs. Even though several reaction mechanisms have been proposed, the catalytic mechanism is still unclear. QM/MM adiabatic mapping calculations were performed in order to investigate roles of this enzyme. High-accuracy SCS-MP2/aVDZ/CHARMM27 calculations indicated that the reaction pathway has three steps; (i) proton transfer from reduced flavin mononucleotide (FMNH2) to D339, (ii) proton transfer from EPSP to FMNH– and (iii) phosphate elimination. Adiabatic mapping calculations indicated that H110 and R48 residues play essential catalyst roles for CS enzyme catalysis by transition state (TS) and product stabilizations via charge polarization and hydrogen bonding to EPSP and/or FMNH2. A high accuracy calculation - SCS-MP2/aVDZ/CHARMM27 method was employed to obtain the accurate reaction mechanism pathway and to evaluate the effect of amino acid residues in the active site on the enzyme catalysis. The potential energy barriers of the reactions of H110A and R48A were found to increase. The CS catalysis was consequently slowed down due to missing the TS and product stabilizations. [Display omitted] •QM/MM modelled the reaction mechanism of chorismate synthase (CS) enzyme catalysis.•High-accuracy SCS-MP2/aVDZ/CHARMM27 calculations indicated that the reaction pathway has three steps.•Catalyst roles for (CS) enzyme catalysis are TS and product stabilizations via charge polarization and hydrogen bonding.•SCS-MP2/aVDZ/CHARMM27 method was employed to obtain the accurate reaction mechanism pathway.